A Silk Sericin/Silicone Nerve Guidance Conduit Promotes Regeneration of a Transected Sciatic Nerve. Issue 15 (1st September 2015) - Xie, Hongjian; Yang, Wen; Chen, Jianghai; Zhang, Jinxiang; Lu, Xiaochen; Zhao, Xiaobo; Huang, Kun; Li, Huili; Chang, Panpan; Wang, Zheng; Wang, Lin
Abstract : Peripheral nerve gap defects lead to significant loss of sensory or motor function. Tissue engineering has become an important alternative to nerve repair. Sericin, a major component of silk, is a natural protein whose value in tissue engineering has just begun to be explored. Here, the first time use of sericin in vivo is reported as a long‐term implant for peripheral nerve regeneration. A sericin nerve guidance conduit is designed and fabricated. This conduit is highly porous with mechanical strength matching peripheral nerve tissue. It supports Schwann cell proliferation and is capable of up‐regulating the transcription of glial cell derived neurotrophic factor and nerve growth factor in Schwann cells. The sericin conduit wrapped with a silicone conduit (sericin/silicone double conduits) is used for bridging repair of a 5 mm gap in a rat sciatic nerve transection model. The sericin/silicone double conduits achieve functional recovery comparable to that of autologous nerve grafting as evidenced by drastically improved nerve function and morphology. Importantly, this improvement is mainly attributed to the sericin conduit as the silicone conduit alone only produces marginal functional recovery. This sericin/silicone‐double‐conduit strategy offers an efficient and valuable alternative to autologous nerve grafting for repairing damaged peripheral nerve. Abstract : Sericin, a natural protein and a major component of silk, is crosslinked to fabricate a novel nerve guidance conduit with physical and chemical properties designed toward optimal nerve regeneration. When this conduit is implanted to a rat sciatic nerve transection model, it effectively promotes peripheral nerve regeneration, leading to significant histological and functional recovery.